Environmental chemical exposures and mental health outcomes in children: a narrative review of recent literature - James, Ashley A.; OShaughnessy, Katherine L. (Frontiers in Toxicology, 2023)
Background: Mental health is an important factor for children's overall well-being. National health statistics show that millions of children are diagnosed with mental health disorders every year, and evidence from studies on chemical pollutants like lead and bisphenols indicate that environmental exposures are linked to mental health illnesses in youth. However, the relationship between children's mental health and the environment is not well understood. This paper aims to review recent literature on prenatal and/or childhood environmental chemical exposures and mental health problems related to mood, anxiety, and behavior. This work also identifies areas of insufficient data and proposes suggestions to fill the data gaps.Methods: A narrative review was performed by searching Google Scholar and PubMed for literature published in the last six years (2017-2022), using search terms related to children, mental health, and environmental chemical exposure. Additional relevant studies were identified by screening the references in these papers.Results: A total of 29 studies are included in this review and results are summarized by chemical category: heavy metals, endocrine-disrupting chemicals, and pesticides. The majority of studies reported positive and significant associations between chemical exposures and child mental health outcomes including internalizing and externalizing behaviors.This review demonstrates that there is a growing body of literature that suggests developmental exposure to some environmental chemicals increases a child's risk of mood, anxiety, and behavior problems. Future research should expand on these findings to understand cumulative impacts, chemical mixtures, neurotoxic mechanisms, sex differences, and windows of vulnerability.